A rapid method for the preparation of an in vitro osteoporosis model of calf vertebrae: histological and biomechanical study - Shi, Anli; Liu, Yijie; Ma, Qiang; Li, Jiaxin; Fan, Jiawang; Ge, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIn vitro biomechanical testing is crucial for the preclinical assessment of novel implant designs. Given the constraints of limited supply and high costs associated with human specimens, calf spines are frequently employed as surrogates for human spines in both in vivo and in vitro biomechanical studies.MethodsThis study selected 60 spinal vertebrae from calves aged between 12 and 18 weeks. The specimens were randomly assigned to two treatment groups, A and B, each comprising 30 specimens. Group A served as the control without decalcification, while Group B underwent decalcification using an 18.3% ethylene diamine tetraacetic acid solution. The impact of decalcification was assessed through histological, imaging, and biomechanical analyses.FindingsDecalcification took approximately 2 months, resulting in osteoporotic vertebrae with a bone mineral density reduction of approximately 50.89% compared to pre-decalcification levels. The bone microstructure was significantly altered, characterized by a decrease in trabecular thickness and number and an increase in trabecular separation. Additionally, the trabecular bone pattern factor (TBPf) and Structure Model Index (SMI) increased. The modulus of elasticity, yield stress, and ultimate stress of the vertebral bodies were all reduced in correlation with the decrease in bone mineral density, demonstrating a strong correlation between these parameters.InterpretationThe data from this study indicate that the decalcification method is effective and capable of rapidly establishing an osteoporotic model suitable for biomechanical testing of clinical devices. This method offers the benefits of ease of operation, reliability, and a controllable degree of osteoporosis.